THE EFFECT OF EMPLOYEE PERCEPTION OF INTERNAL AUDIT ON EMPLOYEE PERFORMANCE WITH CORPORATE GOVERNANCE AS INTERVENING VARIABLES (CASE STUDY AT PT. BIO FARMA COMPANY) - Itsnataani Salima; Nita Kurnia Lestari; Helmy Dwitady Surya; Yuliani Utami Putri; Dini Verdania Latif (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This research aims to analyze the effect of employee perceptions on internal audit on employee performance of PT BIO FARMA (Persero) company with corporate governance as an intervening variable. The sample in this study was 92 employees at the company, using a simple random sampling method. To test the hypothesis using Path Analysis (a combination model of multiple regression models and mediation models), t-test, and F test. The results of the study concluded that employees' perceptions of internal audits have a positive and significant effect on corporate governance and employee performance. Corporate governance also has a positive and significant effect on employee performance. Based on the results of path analysis, it shows that the corporate governance variable is not able to become an intervening variable because the value of the indirect effect of employee perceptions on employee performance through corporate governance is smaller than the direct effect of employee perceptions about the internal audit on employee performance.